Doctoral Students' Perspectives on Their Training as Researchers in Higher Education. Issue 3 (3rd July 2019) - Boyce, B. Ann; Lund, Jackie L.; Napper-Owen, Gloria; Almarode, Danielle
ABSTRACT: The purpose of this article was to examine Kinesiology Doctoral Students' (DS) perspectives on their training as researchers received during doctoral study. Using the Kinesiology Doctoral Student (KDS) survey, 121 current and past DS provided information on nine different aspects related to research training. Specifically, these items consisted of measures of DS perceptions on: (a) establishment of a good foundation for doing independent research and awareness of customary practices related to (i) publishing; (ii) determining authorship; (iii) researching funding; (iv) using data responsibly; (v) reviewing academic papers; (vi) bio-safety, human subjects, and/or animal care; (vii) obtaining research funds; and (viii) enjoyment of conducting research. This topic was viewed through three lenses: (a) status (past and current DS), (b) gender, and (c) sub-disciplines (social and behavior sciences [SBS] research and health/hard sciences [HS] research). The following statistically significant findings were found: (a) understanding practices related to determining authorship ( p > .001), with males reporting a higher mean score [ M = 2.51] than females [ M = 2.08] and (b) understanding practices related to research funding ( p > .05) with the HS ( M = 2.20) showing greater confidence than SBS ( M = 1.91) participants.